About the standardization and quality of laboratory tests aimed at diagnostics and monitoring of tuberculosis chemotherapy - D. V. Vаkhrushevа; I. A. Vаsilyevа (Туберкулез и болезни лёгких)
The article describes the main issues related to the provision of quality of laboratory tests aimed to diagnose tuberculosis and monitor the efficiency of its treatment in the Russian Federation. It speculates on the organization of laboratory diagnostics at all stages, in the laboratories of TB services. Some high priority activities for certification of laboratories have been offered.